Gavagem de NaCl hipertônico induz ingestão de bicarbonato de sódio - Constancio, Juliana (Universidade Federal de São Carlos, 2009)
The literature shows that gavage of 2 M NaCl, a method to induce cell dehydration, induces water and 0.15 M NaCl intake in a two-bottle test. However, the hypertonic NaCl is also known as a mild gastric irritant, which possibly erodes the protective barriers of the gastric mucosa. Therefore, the present work tested the hypothesis that gavage of 2 M NaCl induces mineral intake as a response to gastric irritation. If the gastric irritation is an important factor to induce mineral solution intake, then we can predict that 1) mechanical protectors of the gastric mucosa inhibits the mineral solution intake induced by gavage of NaCl and 2) other irritants such as ethanol and acetic acid, should induce mineral solution intake as the gavage of NaCl did. In previous experiments with adult male Holtzman rats, gavage of 2 M NaCl induced ingestion of appreciable quantities of NaHCO3 and KCl solutions in a five-bottle test (water, 0.01 M KCl, 0.05 mM CaCl2, 0.15 M NaHCO3, 0.15 M NaCl), showing that the effect is not selective for NaCl intake. In subsequent experiments, the animals had access to water and the two preferred mineral solutions (0.01 M KCl and 0.15 M NaHCO3) for ingestion. The ingestion of these solutions was not inhibited by the protective agents of the gastric mucosa, such as aluminum hydroxide, or the NaHCO3, combined with gavage of 2 M NaCl. Non-sodic irritants (50% ethanol or 0.6 N acetic acid) were not able to induce any mineral intake. Furthermore, ethanol - determined by macroscopic inspection as the sole aggressive irritant of the gastric mucosa induced kaolin (hydrated aluminum silicate) intake, a mineral that protects the rat against toxemia-induced malaise. Losartan, an angiotensin II receptor antagonist, injected intracerebroventricularly, inhibited in a dose-response manner the fluid intake induced by gavage of NaCl. The results suggest that NaHCO3 intake induced by gavage of hypertonic NaCl: a) is consistent to cell dehydration rather than to a gastric irritation and b) is mediated by angiotensin II.
Keywords: Fisiologia; Bicarbonato de sódio; Desidratação celular; Preferência mineral; Ingestão de água; Gavagem; Auto-medicação; Thirst; Hypertonic NaCl; CIENCIAS BIOLOGICAS::FISIOLOGIA